Molecular caracterization of a corn core collection–landraces subgroup - Ronaldo Rodrigues Coimbra; Glauco Vieira Miranda; Newton Portilho Carneiro; Cláudia Teixeira Guimarães; Derly José Henriques da Silva; Elainy Cristina Alves Martins Oliveira (Agro@mbiente On-line)
The efficient use of genetic resources- stored in germplasm collections can be maximized if morphoagronomic and molecular information on the accessions is made available. To achieve this, a collection that is well-structured, well-curated and easily accessible (the core collection) is required. Consequently, the objective of the current study was to characterize 80 landrace accessions from the maize core collection of the Federal University of Viçosa (UFV), and assay thenngenetic diversity of the various landraces, considering grain type and ecogeographic origin. For this, AFLP analysis was performed using 12 primer combinations. Genetic diversity of the collection was quantified with the UPGMA method, using the Jaccard Index to quantify dissimilarity. The core collection was divided into four sub-populations by grain type, and into six sub-populations based on ecogeographic origin. Genetic diversity analysis was performed both within and between sub-populations. A high level of genetic variability was found among the landrace accessions of UFV Core Collection, principally among those accessions with dentate type grains.Classification by grain type and ecogeographic origin allowed genetically divergent groups to be distinguished.